Case Report: Thymidine Kinase 2 (TK2) Deficiency: A Novel Mutation Associated With Childhood-Onset Mitochondrial Myopathy and Atypical Progression - Manini, Arianna; Meneri, Megi; Rodolico, Carmelo; Corti, Stefania; Toscano, Antonio; Comi, Giacomo Pietro; Musumeci, Olimpia; Ronchi, Dario (Frontiers in Neurology, 2022)
The nuclear gene TK2 encodes the mitochondrial thymidine kinase, an enzyme involved in the phosphorylation of deoxycytidine and deoxythymidine nucleosides. Biallelic TK2 mutations are associated with a spectrum of clinical presentations mainly affecting skeletal muscle and featuring muscle mitochondrial DNA (mtDNA) instability. Current classification includes infantile- ( ≤ 1 year), childhood- (1–12 years), and late-onset (≥12 years) forms. In addition to age at onset, these forms differ for progression, life expectancy, and signs of mtDNA instability (mtDNA depletion vs. accumulation of multiple mtDNA deletions). Childhood-onset TK2 deficiency typically causes a rapidly progressive proximal myopathy, which leads to wheelchair-bound status within 10 years of disease onset, and severe respiratory impairment. Muscle biopsy usually reveals a combination of mitochondrial myopathy and dystrophic features with reduced mtDNA content. Here we report the case of an Italian patient presenting childhood-onset, slowly progressive mitochondrial myopathy, ptosis, hypoacusis, dysphonia, and dysphagia, harboring the TK2 variants c.278A>G and c.543del, the latter unreported so far. Compared to other childhood-onset TK2-patients, our case displays atypical features, including slowly progressive muscle weakness and absence of respiratory failure, which are usually observed in late-onset forms. This report extends the genetic background of TK2-related myopathy, highlighting the clinical overlap among different forms.